The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1089/gtmb.2011.0098
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Polymorphism −670A>G in the Fas Gene and Serum Markers AST Platelet Ratio Index, AST/ALT with Significant Fibrosis and Cirrhosis in Chronic Hepatitis C

Abstract: Genetic polymorphism -670A>G of Fas gene was associated with significant fibrosis and cirrhosis in chronic hepatitis C patients. APRI and AST/ALT are independent predictors for significant fibrosis. APRI showed a better sensitivity than AST/ALT for prediction of significant fibrosis. Moreover, APRI can be used as an index to exclude liver cirrhosis without performing liver biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Recently, it was found that CD95 rs1800682 A/G polymorphism was potentially associated with significant fibrosis and cirrhosis in chronic HCV patients. 23 , 38 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it was found that CD95 rs1800682 A/G polymorphism was potentially associated with significant fibrosis and cirrhosis in chronic HCV patients. 23 , 38 …”
Section: Discussionmentioning
confidence: 99%
“…The purified PCR products of P53 and CD95 genes were incubated at 37 °C overnight with Bsh1236I and BstNI restriction enzymes respectively to identify three different genotypes of each gene as described in numerous previous studies [ 19 , 20 , 23 , 25 , 38 ] and illustrated in Table 1 . Restriction enzymes were purchased from (Fermentas, Ontario, Canada).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation